Photovoltaic and phototransient interface states properties of nanocomposite Fe3O4-graphene/n-Si/Al photodiode - Alahmed, Z. A.; Phan, D. -T.; Chung, G. -S.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
A photodiode based on Fe3O4-graphene/n-Si/Al diode was fabricated. The electrical and capacitance properties of the diode were investigated by transient current and capacitance measurements. Ag/Fe3O4-graphene/n-Si photovoltaic device gives I-sc of 0.111 mA and V-oc of 375 mV under 1.5 A.M. The maximum electrical power P-max value of the device was found to be 7.567 mu V. This suggests that the studied photovoltaic device can be used as a microvoltage generator. The capacitance of the device increases with illumination. This indicates that the device exhibits a photocapacitance behavior. This behavior was analyzed by transient photocapacitance measurements. The transient interface states density plots of the diode were obtained. The photocapacitance mechanism was explained with the change in the interface states. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Graphene; Photovoltaic device; Diode